2013 IEEE Third Joint International Conference on Development and Learning and Epigenetic Robotics (ICDL) 2013
DOI: 10.1109/devlrn.2013.6652569
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive human robot interaction based on unintentional synchrony: A psycho-experimental study

Abstract: Inspired by studies of interpersonal coordinations, we assumed that unintentional synchrony is a fundamental parameter to initiate and maintain Human Machine interactions. We developed, in our previous works, a neural model allowing a robot to synchronize its behavior depending on the human movement frequency, and thus to choose this interacting partner on the basis of synchrony detection between its own learned dynamics and the visual stimuli induced by the human motion. To confirm or deny our assumptions we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…For example, as referred in [7] "people tend to synchronise their rhythms and movements ... within a conversation". In HRI, it can facilitate the natural interaction with robots with minimal cognitive load [8]. Starting from this knowledge, the features listed below are extracted from the recorded depth videos:…”
Section: Non-verbal Features Extractionmentioning
confidence: 99%
“…For example, as referred in [7] "people tend to synchronise their rhythms and movements ... within a conversation". In HRI, it can facilitate the natural interaction with robots with minimal cognitive load [8]. Starting from this knowledge, the features listed below are extracted from the recorded depth videos:…”
Section: Non-verbal Features Extractionmentioning
confidence: 99%
“…Recently, synchrony started to be investigated in HRI. For example, [32] showed that it can facilitate the natural interaction with robots decreasing the cognitive load of the human partner. Basically, at the present, synchrony was explored in the following three ways: movement synchrony, synchrony of direction (that is opposite direction or same direction), and synchrony towards a specific target (e.g., object, person or location).…”
Section: Nonverbal Behavioral Featuresmentioning
confidence: 99%
“…Empirical research investigating synchrony as a predictor of rapport, similarity, and approval in interpersonal interactions has also been leveraged in the field of human-robot interaction (HRI) (Kendon, 1970 ; Warner, 1992 ; Tickle-Degnen and Gavett, 2003 ; Hasnain et al, 2013 ; Bartneck et al, 2020b ). Recent developments in robotics include making human-robot interactions reflect synchronous interactions between human dyads (Prepin and Revel, 2007 ; Hasnain et al, 2013 ). For example, the adaptable robotics for interaction analysis (ADRIANA) platform enables a robot to detect movements in human users and synchronize its movements automatically in real-time.…”
Section: Introductionmentioning
confidence: 99%